Participatory systems mapping for localised evidence and decision-making: helminth control, SSA. (30th September 2020) - Pearson, G; Parker, M; Storer, E; Allen, T; Fergus, C
Abstract: Background: Evidence-informed decision-making to assist public health practitioners in local-level programme implementation requires adaptive approaches to research, policy and practice. To address these needs there is focus on using participatory methods. Adopting such methods, this research asks: what are the evidence needs of local public health practitioners? How do evidence and decision-making processes interact? We reflect on the process of using Participatory Systems Mapping (PSM) and implications for localising evidence-informed decision-making. Methods: We conducted workshops with district and national-level MoH personnel in Uganda and Malawi using PSM to elicit insights into local modes of schistosomiasis transmission and control, and group discussions on evidence needs and use in implementing control programmes. PSM maps are analysed, triangulated with thematic analysis of group discussion transcripts. Results: Analysing PSM outputs alongside discussions on evidence provides critical methodological and policy insights with implications for localised evidence and decision-making. Further insights into the local dynamics of public health decision-making are gained by triangulating PSM with discussions on the meanings and importance of 'factors' identified. Information which is accessible and useful for local practitioner's decision-making in implementing disease control measures does not always align with academic production and dissemination of evidence, nor across levels where policy is produced or implemented. Conclusions: An array of factors influence local decision-making with implications for global health policies and practices such as for schistosomiasis control. Processes of decision-making and evidence needs of local practitioners need to be better understood within broader context. Evidence and knowledge production on health interventions rarely feedback or respond to local implementation needs, decision-making practices and public health practitioners. Key messages: Processes of decision-making and evidence needs of local practitioners need to be better understood within broader context. Evidence and knowledge production on health interventions rarely feedback or respond to local implementation needs, decision-making practices and public health practitioners.